Effect of concentration of calcium and sulfate ions on gypsum scaling of reverse osmosis membrane, mechanistic study - Mohammad Y. Ashfaq (14152290) (2020)
In seawater reverse osmosis, membrane scaling is one of the major issues affecting its widespread application in the desalination industry. In this paper, the effect of concentration of calcium and sulfate ions from 20 to 150 mM on calcium sulfate scaling of reverse osmosis (RO) and graphene oxide functionalized RO membranes was investigated. It was noted that the permeate flux declined more than 90% when the concentration of ions was increased to 50–150 mM. Principal component analysis was applied to the flux decline over time data, which helped to cluster the data sets based on the extent of membrane scaling at different conditions. The results of scanning electron microscopy showed that the morphology of crystals varied with the concentration from rod shaped to broad rosette structures. Furthermore, it was also found that the membrane surface was fully covered with precipitates, which resulted from both bulk and surface crystallization at higher concentrations of ions in feedwater. The results of X-ray diffraction confirmed that the precipitates formed on the membrane at different concentrations belong to gypsum (CaSO4·2H2O). The results of Fourier Transform Infrared spectroscopy helped to understand the interaction of gypsum with functional groups (−OH, −COOH, CH) of the membrane, which also varied at different concentrations. The contact angle analysis of the scaled membrane was also done to investigate the effect of scaling on the hydrophilicity of the membrane surface, thereby, affecting its inter/intra foulant interactions. Other Information Published in: Journal of Materials Research and Technology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jmrt.2020.09.117